2007 IEEE Congress on Evolutionary Computation 2007
DOI: 10.1109/cec.2007.4424512
|View full text |Cite
|
Sign up to set email alerts
|

Refined runtime analysis of a basic ant colony optimization algorithm

Abstract: Neumann and analyzed the runtime of the basic ant colony optimization (ACO) algorithm 1-Ant on pseudoboolean optimization problems. For the problem OneMax they showed how the runtime depends on the evaporation factor. In particular, they proved a phase transition from exponential to polynomial runtime. In this work, we simplify the view on this problem by an appropriate translation of the pheromone model. This results in a profound simplification of the pheromone update rule and, by that, a refinement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…In [11] it was shown that the expected optimization time of 1-Ant on OneMax is polynomial if ρ = 1 − 1/n with fixed > 0 and in [2] that for ρ = o(1/ log n) it becomes super-polynomial. On the function LeadingOnes the expected optimization time was shown [3] to be quadratic for constant ρ, polynomial for ρ = Ω(1/ log n), and again super-polynomial for ρ = o(1/ log n).…”
Section: Experimental Results For 1-antmentioning
confidence: 99%
See 2 more Smart Citations
“…In [11] it was shown that the expected optimization time of 1-Ant on OneMax is polynomial if ρ = 1 − 1/n with fixed > 0 and in [2] that for ρ = o(1/ log n) it becomes super-polynomial. On the function LeadingOnes the expected optimization time was shown [3] to be quadratic for constant ρ, polynomial for ρ = Ω(1/ log n), and again super-polynomial for ρ = o(1/ log n).…”
Section: Experimental Results For 1-antmentioning
confidence: 99%
“…Additionally, it was observed that for ρ very close to one, 1-Ant exactly simulates the (1+1) EA, which was rigorously analyzed in [6]. In [2] the pheromone model used in [11] was replaced by a simpler, but equivalent model, in which the pheromone values equal the probabilities of ants walking along a particular edge in the construction graph. In [3] an analysis of 1-Ant was carried out for the functions LeadingOnes and BinaryValue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006 by Neumann and Witt [2], Doerr, Neumann, Sudholt, and in 2007 by Witt [10], and Doerr and Johannsen [11] studied a simple algorithm 1-ANT that constructs a pseudo Boolean solution according to a straightforward construction graph where an ant makes independent choices for each bit. The 1-ANT records the best solution found so far.…”
Section: Related Workmentioning
confidence: 99%
“…Investigations on the runtime performance of ACO first started for various pseudo-boolean functions [3,10,11,12] where a simple ACO variant 1-ANT was analysed like (1+1) EA [7]. Another ACO variant MMAS has also been widely investigated for which the phase transition present in 1-ANT due to the evaporation factor does not occur [13,14].…”
Section: Introductionmentioning
confidence: 99%